" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
α + β = -
- 2β + β = - (p + 1)
- β = - (p + 1)
β = p + 1
α = - 2 β
= - 2 (p + 1)
= - 2p - 2
α . β =
(-2p - 2)(p + 1) = - 18
- 2p² - 4p - 2 = - 18
- 2p² - 4p - 2 + 18 = 0
- 2p² - 4p + 16 = 0
p² + 2p - 8 = 0
(p - 2)(p + 4) = 0
p - 2 = 0 atau p + 4 = 0
p = 2 atau p = - 4 (tak memenuhi karena p ≥ 0)
jadi, p = 2
αβ = c/a = -18 -------> α = -18/β
α+2β = 0
-18/β + 2β = 0
-18 + 2β² = 0
2β² = 18
β² = 9
β = 3 atau β=-3
jika β= 3 --> α = -18/3
= -6
sehingga
α+β = -(p+1)
-6+3 = -(p+1)
-3 = -(p+1) --> p+1 = 3
p = 2